STRUCTURAL ELEMENTS OF THE PROCESS OF BUSINESS ENGLISH SKILLS FORMATION IN FUTURE DOCTORS - Людмила Русалкіна (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The article is devoted to the structure and organization of medical students' business English teaching process. The main attention is spared to the problem of creation of the experimental model of future doctors' business English skills formation. The suggested model is aimed at productive mastering of lexical and grammar communicative skills, at formation of business English communicative abilities of students-medics; it has communicative direction and is professionally oriented. The exercises correspond to English language knowledge of the future doctors and are set in sequence of increasing complexity.